Incentive Schemes and Innovative Portfolios - Loyola, Gino; Portilla, Yolanda (Estudios de Economía, 2016)
This article characterizes the properties of the compensation scheme of delegated portfolio management that would lead to the selection of high risk-high return portfolios. In particular, it provides conditions under which a non-monotone payment structure emerges as an optimal contract, which rewards extreme results and punishes moderate ones.